Pathogen‐inducible Ta‐Lr34res expression in heterologous barley confers disease resistance without negative pleiotropic effects. Issue 1 (11th July 2017) - Boni, Rainer; Chauhan, Harsh; Hensel, Goetz; Roulin, Anne; Sucher, Justine; Kumlehn, Jochen; Brunner, Susanne; Krattinger, Simon G.; Keller, Beat
Summary: Plant diseases are a serious threat to crop production. The informed use of naturally occurring disease resistance in plant breeding can greatly contribute to sustainably reduce yield losses caused by plant pathogens. The Ta ‐ Lr34res gene encodes an ABC transporter protein and confers partial, durable, and broad spectrum resistance against several fungal pathogens in wheat. Transgenic barley lines expressing Ta ‐ Lr34res showed enhanced resistance against powdery mildew and leaf rust of barley. While Ta ‐ Lr34res is only active at adult stage in wheat, Ta ‐ Lr34res was found to be highly expressed already at the seedling stage in transgenic barley resulting in severe negative effects on growth. Here, we expressed Ta ‐ Lr34res under the control of the pathogen‐inducible Hv ‐ Ger4c promoter in barley. Sixteen independent barley transformants showed strong resistance against leaf rust and powdery mildew. Infection assays and growth parameter measurements were performed under standard glasshouse and near‐field conditions using a convertible glasshouse. Two Hv ‐ Ger4c::Ta‐Lr34res transgenic events were analysed in detail. Plants of one transformation event had similar grain production compared to wild‐type under glasshouse and near‐field conditions. Our results showed that negative effects caused by constitutive high expression of Ta ‐ Lr34res driven by the endogenous wheat promoter in barley can be eliminated by inducible expression without compromising disease resistance. These data demonstrate that Ta ‐ Lr34res is agronomically useful in barley. We conclude that the generation of a large number of transformants in different barley cultivars followed by early field testing will allow identifying barley lines suitable for breeding.